Kesiapan Pelepasliaran Orangutan Kalimantan (Pongo pygmaeus) Usia 8 tahun di Sekolah Hutan II Pusat Rehabilitasi BOSF Samboja Lestari, Kalimantan Timur - Herma Sunaryo, Praniti
The Bornean orangutan (Pongo pygmaeus) population is steadily declining due to high habitat destruction and poaching, causing the species to be classified as endangered. Rehabilitation aims to maintain orangutan population by releasing the orangutan back into the wild. The main objective of this research is to assess the pre-release readiness of orangutans based on several parameters, which are the activity budget, diet, height strata usage for arboreal activity, and home range. The study was conducted at the Forest School II BOSF Samboja Lestari Rehabilitation Center, East Kalimantan in April-June 2019. Observation was done for eight-year-old orangutans named Elaine, Elder, Edgar and Anna Friel. Data collection for assessing daily activity budget, diet, and height strata usage was conducted through focal-instantaneous sampling every two minutes for 5-6 hours each day starting from 09:00 a.m. The home range was measured using Minimum Convex Polygon (MCP) in ArcMap 10.4.1 which is based on each orangutan’s travelling distance recorded by the tracking feature of the GPS receiver. To see the readiness for release, a comparison was made between the four orangutans and the BOSF ex-rehabilitant orangutans by looking at the parameters of activity budget, natural diet consumption, arboreal activity, and daily home range. Based on a 203.48-hour observation, it was found that Elaine, Elder, and Anna Friel have a high time allocation for resting activities, while Edgar has a high time allocation for moving activities. Diet consumed consisted of 18 types of feed from technicians, 30 species of natural plant-based food items, and 3 other types of diet encompassing water, termites, and soil. The type of diet with the highest consumption proportion is pith for Elder, pulp for Anna, and feed from technicians for Elaine and Edgar. For the arboreal activity, Elaine and Edgar have the highest proportion of using 0 meters of strata height, while Elder and Anna have the highest proportion of using 5-10 meters of strata height. The results of the MCP analysis show that the home range of Elaine is 4.95 ha, Elder is 7.47 ha, Edgar is 6.17 ha, and Anna Friel is 7.42 ha. It can be concluded that Elaine, Elder, Edgar, and Anna Friel are not ready to be released because they still have a low proportion of feeding activity, low strata height usage for arboreal activity (in Elaine and Edgar), and low consumption of natural diet and narrow home range area.